Paleomagnetism of the Deadman's Bay diabase dikes from northeastern central Newfoundland - Murthy, G. S. (Canadian Journal of Earth Sciences, 1983)
Twenty-six oriented samples were collected from six diabase dikes cutting the Deadman's Bay granite of northeastern central Newfoundland for the purpose of paleomagnetic investigations. The dikes probably form part of a general swarm of diabase dikes in this area of Devonian age ( 40 Ar/ 39 Ar age of 370 ± 10 Ma). Stepwise thermal demagnetization of individual specimens followed by vector subtraction based on Zijderveld plots revealed two characteristic magnetizations: one, a poorly grouped magnetization of [Formula: see text], Ī = 78.0°, α 95 = 17.4°, κ = 16 carried by multidomain magnetite; and a better grouped magnetization of [Formula: see text], Ī = 4.0°, α 95 = 10.0°, κ = 42 residing in hematite. A baked contact test of the host rock (Deadman's Bay granite) intruded by the diabase dikes revealed a steep well grouped magnetization, which is not dissimilar to that carried by magnetite in the dikes. The magnetization of the host rock seems to be well grouped irrespective of distance away from the dike, thus making the contact test inconclusive. It is not certain which, if any, of the two obtained poles corresponds to the (primary) age of intrusion of the dikes. The paleopole based on magnetite's magnetization, called the DB1 pole, is in the same general vicinity as some "anomalous" pole positions for intrusives from Newfoundland and New Brunswick. The paleopole based on hematite's magnetization, called the DB2 pole, happens to be the first one from eastern Newfoundland that agreed within error limits with the Acadian poles. The poles from diabase dikes of the Gander Zone are discussed in the context of other poles from the northern Appalachians. It is concluded that the Devonian poles from Acadia seem to be displaced relative to the cratonic North American poles for that age. However, critical testing for the confirmation of such a displacement during the Devonian had to wait a clearer definition of the positions of the poles and their ages. It was shown that such a displacement, if present during the ...